Changes in plant-soil synergistic patterns along grassland degradation gradients in northern China - Zhao, Feiyan; Meng, Zhongju; Ren, Xiaomeng; Dang, Xiaohong; Shi, Shiling; Li, Peng; Ding, Hailong; Guo, Jingjie (Frontiers in Environmental Science, 2024)
Inner Mongolia's grassland is one of the most complete natural grasslands for ecological diversity and biodiversity conservation in the world. However, its degradation has seriously affected the plateau's sustainable development and grassland restoration and reconstruction. To reveal the response of soil-plant synergistic relationship to different degrees of degradation, we selected three degrees of degradation (total coverage of vegetation:20%-30%, LD), moderate degradation (total coverage of vegetation:10%-20%, MD) and severe degradation (total coverage of vegetation:＜0%, SD) on typical grasslands in Inner Mongolia (3 transects per degraded plot, 3 replicates per transect, a total of 27 quadrats).Correspondence between vegetation and soil under different degrees of degradation was obtained by correlation analysis. Soil physical properties influence degradation degree much more than soil depth. Among them, the most obvious total nitrogen (TN) decreased by 251.63 % and 125.81 % under moderate degradation(MD) and severe degradation(SD), respectively, compared with light degradation(LD). When the degree of degradation increased, the number of species reduced, and when compared to light degradation, moderate degradation and severe degradation decreased by 52.38% and 66.67%, respectively. The declining trend in the number of species was also indicated by Simpson, Margalef, and Shannon-Winener in addition to the Pielou index. The synergy between plant diversity index and soil organic matter (SOM), available potassium (AK) and bacteria was relatively strong.